Angptl7 promotes insulin resistance and type 2 diabetes mellitus by multiple mechanisms including SOCS3‐mediated IRS1 degradation. Issue 10 (12th August 2020) - Xu, Tong; Xu, Lilei; Meng, Panpan; Ma, Xuqian; Yang, Xiaoqing; Zhou, Yaru; Feng, Mingqian
Abstract: Angptl7 is a secreted and circulating cytokine that belongs to Angiopoietin‐like family. The current knowledge about the function of Angptl7 is still limited, and its biological role is only marginally known, such as in the promotion of angiogenesis and inflammation. Here, we demonstrated that Angptl7 promotes insulin resistance and type 2 diabetes mellitus (T2DM). We found that the circulating Angptl7 levels in T2DM patient and mouse models were significantly elevated. Artificial overexpression of Angptl7 in hepatic cells inhibited glucose uptake and impaired insulin signaling pathway. Furthermore, in vivo overexpression of Angptl7 in experimental healthy mice also caused insulin resistance‐like characteristics. Mechanistic studies revealed that Angptl7 can upregulate SOCS3 expression, leading to the IRS1 degradation in proteasome. Furthermore, over‐expressed Angptl7 inhibited the phosphorylation of Akt and promoted the phosphorylation of ERK1/2, which was known to be associated with insulin resistance. Taken together, our study provided strong evidence that Angptl7 promotes insulin resistance and T2DM by multiple mechanisms, which made Angptl7 a new potential therapeutic target for treatment of insulin resistance and T2DM.